2019
DOI: 10.3390/coatings9100626
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Modeling Studies of Bond Coat Species Effect on Microstructure Evolution in EB-PVD Thermal Barrier Coatings in Cyclic Thermal Environments

Abstract: In this work, the effects of bond coat species on the thermal barrier coating (TBC) microstructure are investigated under thermal cyclic conditions. The TBC samples are prepared by electron beam-physical vapor deposition with two species of bond coats prepared by either air-plasma spray (APS) or high-velocity oxygen fuel (HVOF) methods. The TBC samples are evaluated in a variety of thermal cyclic conditions, including flame thermal fatigue (FTF), cyclic furnace thermal fatigue (CFTF), and thermal shock (TS) te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 23 publications
(25 reference statements)
0
0
0
Order By: Relevance
“…Nonetheless, the TGO layer may increase the internal stress in the TBC system, hence potentially originating cracking at the interface between the bond and top coats. This phenomenon may eventually lead to the unwanted spallation or delamination of the top coat in service [46,47,53].…”
Section: Tbc Structure Fabrication Techniques and Failure Mechanismsmentioning
confidence: 99%
“…Nonetheless, the TGO layer may increase the internal stress in the TBC system, hence potentially originating cracking at the interface between the bond and top coats. This phenomenon may eventually lead to the unwanted spallation or delamination of the top coat in service [46,47,53].…”
Section: Tbc Structure Fabrication Techniques and Failure Mechanismsmentioning
confidence: 99%
“…Moreover, many processes have been employed to deposit bondcoat, such as APS, low-pressure plasma spray, and high-velocity oxygen fuel (HVOF) [27]. The APS technique is the most popular to form bondcoat due to its economic benefits; however, the HVOF process is more desirable to increase the working temperature and fuel performance in gas turbines and diesel engines [28,29]. According to Lu et al, more extended thermal durability was found in HVOF bondcoat than in the APS bondcoat due to lower equivalent stress at the TGO layer [28].…”
Section: Introductionmentioning
confidence: 99%
“…The APS technique is the most popular to form bondcoat due to its economic benefits; however, the HVOF process is more desirable to increase the working temperature and fuel performance in gas turbines and diesel engines [28,29]. According to Lu et al, more extended thermal durability was found in HVOF bondcoat than in the APS bondcoat due to lower equivalent stress at the TGO layer [28]. However, most HVOF bondcoating does not focus on the phase transformation of alumina in TGO and the stress-induced at the interface of topcoat and bondcoat simultaneously.…”
Section: Introductionmentioning
confidence: 99%